Stability problems lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Bressanone (Bolzano), Italy, June 2-11, 1974 - Salvadori, Luigi (C.I.M.E. Summer Schools, 2011)
Stabilité asymptotique pour des problèmes de perturbations singulières.- J.K. Hale: Stability of linear systems with delays.- V. Lakshmikantham: Stability and asymptotic behaviour of solutions of differential equations in a Banach space.- P. Negrini: On a definition of total stability for continuous or discrete dynamical systems.-N. Rouche: Théorie de la stabilité dans les équations différentielles ordinaires.- E.O. Roxin: Stability and differ